Dampak Zakat Produktif Terhadap Kesejahteraan Masyarakat dalam Perspektif CIBEST Model Berbasis Maslahah: Studi pada Program BAZNAS Kabupaten Sinjai - Syamsul Syamsul; M. Wahyuddin Abdullah; Irwan Misbach (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the contribution and impact of productive zakat on community welfare in Sinjai Regency using the maslahah-based CIBEST model. Historically, measuring the success of productive zakat has focused primarily on increasing the income of mustahik (zakat recipients), while spiritual and social aspects have not been comprehensively integrated. The study employs a qualitative field research approach involving mustahik recipients of productive zakat. Data were collected through in-depth interviews, observation, and documentation, with key informants comprising mustahik and staff from BAZNAS Sinjai Regency. The data were analyzed using data reduction, data presentation, and conclusion drawing, utilizing triangulation techniques. The results indicate that the productive zakat program implemented by BAZNAS in Sinjai Regency has made a positive contribution and impact on the mustahik. Materially, productive zakat has succeeded in increasing the income and purchasing power of the mustahik. Spiritually, it fosters improved religious observance, gratitude, honesty, and a sense of responsibility in business management. Socially, it creates a better quality of life by enhancing social utility and social concern. Furthermore, the maslahah perspective demonstrates the achievement of maqashid al-shari'ah (objectives of Islamic law) goals, particularly the preservation of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-'aql), lineage (hifz al-nasl), and wealth (hifz al-mal). The implications of productive zakat extend beyond achieving economic independence—transforming mustahik into muzakki (zakat payers) and serving as a sustainable stimulus rather than merely meeting short-term needs—to also fostering gratitude, religious obedience, optimism, reduced social inequality, and social solidarity.